2011
DOI: 10.1016/j.niox.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

RNA splicing in regulation of nitric oxide receptor soluble guanylyl cyclase

Abstract: Soluble guanylyl cyclase (sGC) is a key protein in the nitric oxide (NO)/-cGMP signaling pathway. sGC activity is involved in a number of important physiological processes including smooth muscle relaxation, neurotransmission and platelet aggregation and adhesion. Regulation of sGC expression and activity emerges as a crucial factor in control of sGC function in normal and pathological conditions. Recently accumulated evidence strongly indicates that the regulation of sGC expression is a complex process modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…4, A and B). Interestingly, the predominant form of sGC-␣1 expressed in the RFL-6 cells was a truncated splice variant of 52 kDa, probably similar to the ⌬1-239 splice variant that is expressed in BE2 neuroblastoma cells and in lung tissue, which is missing a portion of the ␣ subunit N-terminal regulatory domain (19,20). The mass distribution of ⌬1-239 sGC-␣1 in the cell supernatant was broad and similar to that of the sGC-␤1 subunit, consistent with the truncated sGC-␣1 subunit and the sGC-␤1 subunit still being able to combine and form an active heterodimer in cells (19,20).…”
Section: E and F)mentioning
confidence: 95%
“…4, A and B). Interestingly, the predominant form of sGC-␣1 expressed in the RFL-6 cells was a truncated splice variant of 52 kDa, probably similar to the ⌬1-239 splice variant that is expressed in BE2 neuroblastoma cells and in lung tissue, which is missing a portion of the ␣ subunit N-terminal regulatory domain (19,20). The mass distribution of ⌬1-239 sGC-␣1 in the cell supernatant was broad and similar to that of the sGC-␤1 subunit, consistent with the truncated sGC-␣1 subunit and the sGC-␤1 subunit still being able to combine and form an active heterodimer in cells (19,20).…”
Section: E and F)mentioning
confidence: 95%
“…Alternative splicing of ␣1 and ␤1 sGC can potentially affect the composition, abundance, and functional properties of sGC protein isoforms expressed in blood vessels. Previous studies demonstrated the expression of human sGC splice forms in cell culture models (42). To investigate whether ␣1 and ␤1 sGC splice forms are expressed in human vascular tissue, we obtained aortic specimens from donors deceased from causes unrelated to aortic dysfunction (Capital Biosciences).…”
Section: Expression Of ␣1 and ␤1 Sgc Splice Forms In Human Aortamentioning
confidence: 99%
“…β1-iso 4 (β1Δ 68Ω643) [42] βCAT CC β -PAS HNOX 392 β1-Tr4 βCAT CC β -PAS HNOX β1-Tr5 β1-iso 5 (β1Δ 33) [42] Protein isoform*:…”
Section: ω43 Aamentioning
confidence: 99%
See 1 more Smart Citation
“…The nitric oxide (NO)-soluble guanylyl cyclase (sGC)-cGMP pathway has been implicated in a variety of biological processes, such as vasodilatation, inhibition of platelet aggregation and leukocyte adhesion, neuromodulation and neurotransmission (Sharina et al, 2003;Sharina et al, 2011). To mediate these effects, endogenous and exogenous NO binds to the ferrous iron of sGC heme prosthetic group, triggering a conformational change of sGC followed by the activation of the sGC enzyme.…”
Section: Introductionmentioning
confidence: 99%